Influence of mitral transcatheter edge-to-edge repair in patients with severe mitral regurgitation on left ventricle function - M. I. Makeev; M. A. Saidova; T. E. Imaev (Российский кардиологический журнал, 2024)
Aim. To study the changes of left ventricular (LV) contractile function in patients with severe mitral valve (MV) insufficiency with assessment of global longitudinal strain (GLS) indicators and LV myocardial function after the mitral transcatheter edge-to-edge repair (TEER) within 12-month follow-up.Material and methods. The study consisted of 43 patients with severe mitral regurgitation (MR) as follows: 23 patients with functional MR (FMR), 20 patients with degenerative MR (DMR). A comprehensive echocardiographic study, including speckle tracking echocardiography, was performed at baseline, 4-5 days, 6 and 12 months after TEER. Standard structural and functional indicators of the LV, LV GLS and myocardial performance parameters were assessed.Results. The early postoperative period (4-5 days) was characterized by a decrease in global constructive work (GCW) (FMR group — from 977 [684; 1253] to 857 [736; 1488] mm Hg%, (p=0,038); DMR group — from 1458 [1283; 1848] to 1350 [1010; 1488] mm Hg% (p=0,011)), an increase in global wasted work (GWW) (FMR group — from 177 [130; 280] to 336 [242; 388] mm Hg% (p=0,004); DMR group — from 128 [81; 172] to 216 [164; 279] mm Hg% (p=0,043)), which was accompanied by a decrease in myocardial efficiency (FMR group — from 81,5 [77; 87] to 76 [73; 79]%, (p=0,021); DMR group — from 90 [85; 93] to 82 [79; 85]% (p=0,018)). After 12-month follow-up, there was a significant increase in GCW relative to the initial values in both cohorts of patients as follows: FMR group — to 1128 [890; 1711] mm Hg% (p=0,048); DMR group — to 1818 [1478; 2034] mm Hg% (p<0,001). There was also an increase in GWW in the FMR group to 255 [214; 363] mm Hg% (p=0,024) and in the DMR group to 230 [140; 270] mm Hg% (p=0,043). There were no significant improvement of LV GLS in both groups.Conclusion. The early postoperative period after TEER was characterized by a temporary deterioration in all LV performance parameters, which recovered by 6 and 12 months of follow-up. Myocardial function restoration by one year of follow-up was noted due to an increase in GCW. LV GLS and ejection fraction did not change significantly by 1 year of follow-up compared to baseline values.